Developments in the modelling of spray forming - Grant, P (Inst of Materials, 1997)
Quality of products is very important problem. Application of spray forming allows to manufacture the high-quality products. Modelling has always been recognized as important feature at International Conferences on Spray forming. Doctor P. Grant places discussion at the 3rd Conference in this context and suggests ways in which improved models will contribute to further commercial and technological development. At all stages of the process, experimental measurements of material mass or heat flow are difficult and numerical modelling has been used to provide required information. Modelling of material losses because of droplet overspray, bounce off, and rejected billets due to excessive porosity gives reasonable good agreement with experimental data.